Markers of Inflammation and Infection in Sepsis and Disseminated Intravascular Coagulation. (15th April 2019) - Patel, Priya; Walborn, Amanda; Rondina, Matthew; Fareed, Jawed; Hoppensteadt, Debra
Sepsis is a severe systemic inflammatory response to infection that manifests with widespread inflammation as well as endothelial and coagulation dysfunction that may lead to hypotension, organ failure, shock, and death. Disseminated intravascular coagulation (DIC) is a complication of sepsis involving systemic activation of the fibrinolytic and coagulation pathways that can lead to multi-organ dysfunction, thrombosis, and bleeding, with a 2-fold increase in mortality. This study demonstrates the diagnostic and prognostic value of profiling various biomarkers of inflammation and infection in patients with sepsis-associated DIC to assess the severity of illness. Deidentified samples were obtained from adult patients with sepsis and suspected DIC. Platelet count, prothrombin time, D-dimer, and fibrinogen levels were used to assign International Society of Thrombosis and Hemostasis DIC scores to plasma samples from 103 patients with sepsis and suspected DIC. Using commercially available enzyme-linked immunosorbent assay, chromogenic assay, and RANDOX Biochip methods, levels of procalcitonin (PCT), extracellular nucleosomes, interleukin (IL) 6, IL-8, IL-10, and tumor necrosis factor α (TNFα) were measured in patients with sepsis and DIC and compared to levels in healthy individuals. Elevated levels of PCT, IL-6, IL-8, IL-10, and TNFα were observed in most patients with sepsis and DIC. Additionally, the levels of these markers show significant positive correlations with each other and with DIC score. Currently, no single biomarker can effectively diagnose DIC in patients with sepsis. This study lays the groundwork for the development of a diagnostic algorithm using several markers of inflammation and infection and DIC score as parameters in assessing severity of sepsis-associated coagulopathy in a clinical setting.